2014
DOI: 10.1371/journal.pone.0112626
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonamide-Resistant Bacteria and Their Resistance Genes in Soils Fertilized with Manures from Jiangsu Province, Southeastern China

Abstract: Antibiotic-resistant bacteria and genes are recognized as new environmental pollutants that warrant special concern. There were few reports on veterinary antibiotic-resistant bacteria and genes in China. This work systematically analyzed the prevalence and distribution of sulfonamide resistance genes in soils from the environments around poultry and livestock farms in Jiangsu Province, Southeastern China. The results showed that the animal manure application made the spread and abundance of antibiotic resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 25 publications
3
55
0
2
Order By: Relevance
“…In ADS, sul1 (21.2 %) was the ARG with high relative abundance, while the intI genes could not be detected using a metagenomics approach. These findings are consistent with previous studies reporting prevalence of sul1 and sul genes in agriculture impacted environments [37,38]. Other abundant genes in ADS included mexB (7.0 %) and mexY (8.5 %), aadA1 (6.1 %) and strB (6.6 %).…”
Section: Diversity and Distribution Of Antibiotic Resistance Genes Insupporting
confidence: 92%
“…In ADS, sul1 (21.2 %) was the ARG with high relative abundance, while the intI genes could not be detected using a metagenomics approach. These findings are consistent with previous studies reporting prevalence of sul1 and sul genes in agriculture impacted environments [37,38]. Other abundant genes in ADS included mexB (7.0 %) and mexY (8.5 %), aadA1 (6.1 %) and strB (6.6 %).…”
Section: Diversity and Distribution Of Antibiotic Resistance Genes Insupporting
confidence: 92%
“…Based on culture-dependent approaches, sulfonamide-resistant bacteria isolated from agriculture sites contaminated by sulfonamides incorporated mainly Bacillus genera (49). Similarly, Bacillus has been found to be the most prevalent genus for all sulfonamide-resistant bacteria isolated from manure samples (50). In another study, a phylogenetic analysis further showed that there were possibilities for the genetic transfer of the sul1 gene from intestinal Enterococcus spp.…”
Section: Fig 5 Network Analyses As Inferred By Pairwise Spearman Corrmentioning
confidence: 95%
“…A larger number of studies have shown that manure application is a major source of agricultural soil contamination with veterinary pharmaceuticals (Christian et al, 2003;Karcı & Balcıoğlu, 2009;Wang et al, 2014). Such findings are necessary for an evidence-based risk assessment of the effects of veterinary pharmaceuticals in the environment and subsequent policies and regulatory measures aiming to monitor and minimise these effects (Kaczala & Blum, 2016).…”
Section: Thielementioning
confidence: 99%